Analysis of an interleaved control scheme employed in split source inverter based grid‐tied photovoltaic systems. Issue 6 (23rd February 2021) - Nannam, Hari Charan; Banerjee, Atanu; Guerrero, Josep M.
Abstract: In conventional grid‐tied renewable energy applications, the dc–dc converter is inevitable. An increased cost, size, and reduced efficiency are the demerits of incorporating a dc–dc converter. A recently introduced split source inverter (SSI) is capable to perform both dc–dc as well as dcac at a time. The main attractive controllable feature of SSI is its modulation index. By utilizing this parameter, an interleaved control structure is proposed for the SSI in grid‐tied photovoltaic applications. The main objectives of the work are to track peak power and to maintain a stabilized voltage across the dc‐link capacitor at a variable load and grid disturbances. The proposed peak power controller performs two important actions: (i) the peak power is traced at all irradiance and (ii) generates a duty cycle to enhance the dc‐link capacitor voltage. The proposed scheme is essentially investigated with simulation. To validate experimentally, a 1 KW photovoltaic system is integrated into a grid‐tied 10 kVA SSI prototype. A Xilinx based Spartan field‐programmable gate array (FPGA) is used to provide a control algorithm for the SSI. Few case studies at different conditions are performed and investigated. Experimental and simulation results are presented to prove the robustness of the control strategy.